Potret Perempuan Suku Dani dalam Pembangunan di Kabupaten Jayawijaya Papua - Vince Tebay (Pusat Studi Wanita, Univesitas Kristen Indonesia, 2020)
Abstract: This study attempts to seekhow well the extentof involvement Dani womenhaveintaking part in the development in Jayawijaya Regency. The focus of this research is to find out the extent of involvement of Dani women in Education, Health, Economy, and Social Sectors. The result of this study indicates that Dani women, viewed from the level of Education, Health, Economy, and Social Sectors have not been directly involved, but only a few involved in the four aspects studied. This is because the workload of women in the domestic sphere is far more than that of men, thus consuming women's time and energy. Besides that, the culture and mutual power are also quite high compared to other regions in Papua. The method used in this research is descriptive qualitative method. The purpose of this study was to determine the situation of Dani women based on their involvement in aspects of Education, Health, Economy and Social sectors. The conclusion from this study shows that the participation of Dani women in four aspects of development in Jayawijaya Regency is still very low. Also the Government does not yet have complete disaggregated data between women and men to support the development of existing development processes. Key Words: Women, Dani Tribe, Development, Jayawijaya Regency